Quantifying the economic impact of soil constraints on Australian agriculture: A case‐study of wheat. (14th September 2018) - Orton, Thomas G.; Mallawaarachchi, Thilak; Pringle, Matthew J.; Menzies, Neal W.; Dalal, Ram C.; Kopittke, Peter M.; Searle, Ross; Hochman, Zvi; Dang, Yash P.
Abstract: Soil sodicity, acidity, and salinity are important soil constraints to wheat production in many cropping regions across Australia, and the Australian agricultural industry needs accurate information on their economic impacts to guide investment decisions on remediation and minimize productivity losses. We present a modelling framework that maps the effects of soil constraints on wheat yield, quantifying forfeited wheat yields due to specific soil constraints at a broad spatial scale and assessing the economic benefit of managing these constraints. Of the three soil constraints considered (sodicity, acidity, and salinity), sodicity caused the largest magnitude of yield gaps across most of the wheat‐cropping areas of Australia, with an average yield gap of 0.13 t ha −1 yr −1 . Yield gaps due to acidity were more concentrated spatially in the high‐rainfall regions of Western Australia, Victoria, and New South Wales, and averaged 0.04 t ha −1 yr −1 across the wheat‐cropping areas of Australia, whereas the yield gap due to salinity was estimated to be 0.02 t ha −1 yr −1 . The lost opportunity associated with soil sodicity for wheat production was estimated to be worth A$1, 300 million per annum, for soil acidity, A$400 million per annum, and for salinity, A$200 million per annum. The results of this work should prove useful to guide national investment decisions on the allocation of resources and to target areas where more detailed information would be required in order to reduce the yield gap associated with soil constraints on wheat yields in Australia.